The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.2165/00002018-199717010-00004
|View full text |Cite
|
Sign up to set email alerts
|

Drug Administration in Chronic Liver Disease

Abstract: Cirrhosis encompasses a range of pathophysiological changes that may alter drug disposition. Drugs that are dependent primarily on the liver for their systemic clearance are more likely to be subject to reduced elimination and subsequent accumulation. Drug accumulation may lead to excessive plasma drug concentrations and adverse effects, if the adverse effects of the drug are concentration-dependent. The effects of hepatic insufficiency on the pharmacokinetics of drugs are not consistent or predictable. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
72
1
2

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(75 citation statements)
references
References 204 publications
0
72
1
2
Order By: Relevance
“…In four drugs (2.2%) (dacarbazine, leuprorelin, maraviroc and zidovudine) no information in the previously mentioned databases was found nor in further bibliography searches. That is why a theoretical adjustment recommendation based on the proposal defined by Delcò et al (1) From the 191 reviewed drugs, E H was calculated with the Westphal et al formula (13) in 103 drugs (53.9%); in 66 drugs (34.6%) it was not obtained due to lack of data; in 22 drugs (11.5%) E H was obtained through the bibliography.…”
Section: Resultsmentioning
confidence: 99%
“…In four drugs (2.2%) (dacarbazine, leuprorelin, maraviroc and zidovudine) no information in the previously mentioned databases was found nor in further bibliography searches. That is why a theoretical adjustment recommendation based on the proposal defined by Delcò et al (1) From the 191 reviewed drugs, E H was calculated with the Westphal et al formula (13) in 103 drugs (53.9%); in 66 drugs (34.6%) it was not obtained due to lack of data; in 22 drugs (11.5%) E H was obtained through the bibliography.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, the liver plays a central role in the pharmacokinetics of many drugs. Liver dysfunction may not only reduce the plasma clearance of a number of drugs eliminated by biotransformation and/or biliary excretion, but it can also affect plasma protein binding which in turn could influence the processes of distribution and elimination [12,13]. Liver disease has major effects on drug response, of which prescribers should be aware to ensure safe and effective therapy [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…During other liver disease states, such as septic cholestasis, obstructive cholestasis, and alcoholic and viral hepatitis, human and rodent studies have demonstrated alterations in cytochrome P450-mediated drug metabolism, transport, and pharmacokinetics (Forrest et al, 1977;Farrell et al, 1978Farrell et al, , 1979Narang et al, 1981Narang et al, , 1982Narang et al, , 1985Figg et al, 1995;Westphal and Brogard, 1997;Kubitz et al, 1999;Nadai et al, 2001;Congiu et al, 2002). However, there is little information on the effect of NAFLD on these same parameters.…”
mentioning
confidence: 99%